ANALISIS KESALAHAN KONSTRUKSI SINTAKSIS PADA TULISAN KOLOM OPINI DI PONTIANAK POST VERSI DARING - Voni Suciati; Patriantoro Patriantoro; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the form of syntactic construct errors. The results of the analysis of this study found that there were errors caused by several things, namely language errors in the syntactic aspect, including 8 errors in phrase aspect and 25 errors in sentence aspects. Phrase errors include incorrect wording and incomplete elements of the phrase. Sentence construction errors are divided into 2 parts, namely the use of sentence functions (5 category) and choice of prepositions and use of conjunctions (4 category). The first category, namely the improper compositions of the subject functions, the absence of elements of the predicate functions, improper use of predicate functions, excessive use of predicate functions, and incomplete sentences or absence of free clauses in compound sentences. The second category is the incorrect choice of prepositions, the absence of prepositions, improper use of conjunctions, and use of multiple or excessive elements.Keywords: construction, syntax, phrase, clause, sentence, opinion.